Influence of use of a bipolar vessel sealing device on short‐term postoperative mortality after splenectomy: 203 dogs (2005‐2018). Issue 2 (14th December 2019) - Sirochman, Anna L.; Milovancev, Milan; Townsend, Katy; Grimes, Janet A.
Abstract: Objective: To compare short‐term postoperative mortality in dogs after splenectomy performed with or without a bipolar vessel sealing device (BVSD) and to identify variables associated with mortality. Study design: Retrospective study. Sample population: Client‐owned dogs (n = 203). Methods: Medical records of dogs that underwent splenectomy from 2005‐2018 were reviewed. Mortality rates were compared between dogs that underwent splenectomy with or without BVSD. Causes of death and variables associated with short‐term mortality were assessed. Results: Fifteen of 203 (7.4%) dogs died prior to discharge, and seven (3.4%) dogs died prior to suture removal for a total short‐term mortality rate of 22 of 203 (10.8%). The estimated difference in proportion of deaths prior to discharge between the BVSD and non‐BVSD groups was −0.01 (95% confidence interval = −0.08 to 0.06). Duration of anesthesia was longer when splenectomy was performed without BVSD (median 168 vs 152 minutes; P = .03). Multivariate analysis identified intraoperative (odds ratio [OR] 5.7) or postoperative (OR 13.6) administration of blood products, increasing duration of anesthesia (OR 1.15 per additional 16 minutes), and intraoperative ventricular arrhythmias (OR 6.8) as significantly associated with death prior to discharge. Intraoperative (OR 3.2) or postoperative (OR 7.7) administration of blood products was associated with death prior to suture removal. Conclusion: Use of a BVSD did not appear to increase short‐term mortality after splenectomy. Clinical significance: Dogs undergoing splenectomy that require intraoperative or postoperative transfusions, experience intraoperative ventricular arrhythmias, or have prolonged anesthesia may be at risk for death in the short‐term postoperative period.